Diskurssintutkimus - monitieteinen ja monimenetelmäinen ala - Lotta Lehti; Lauri Haapanen; Liisa Kääntä (Suomen Soveltavan Kielitieteen Yhdistys AFinLA ry, 2022)
There is a growing interest towards metatheoretical examination of linguistic research. This special issue contributes to this examination from the perspective of discourse studies. The issue consists of seven articles which present methods in different areas of discourse studies. The aim of this introductory article is firstly to define the notions of discourse and method. Secondly, through the presentation of the articles of the issue, we present a variety of methods pertaining to different stages of research. In particular, methods of data collection and classification, as well as of data analysis, are presented. We conclude the article with some remarks on the future avenues of the methodology of discourse studies.
Diskurssintutkimuksen menetelmistä. On the methods in discourse studies